Renal cell -like carcinoma of the nasal cavity: a case report and review of the literature - Zhenwei-Chen (Diagn Pathol, 2017)
BACKGROUND: Sinonasal renal cell-like carcinoma (SRCLC) is an extremely rare low malignant tumor arising in the sinonasal tract, with histological mimicry of renal cell carcinoma. CASE PRESENTATION: We present a case of sinonasal renal cell-like carcinoma in a 63-year-old male patient. Computer tomography(CT) scanning revealed a soft tissue mass at the left nasal cavity and choana. Histologically, the predominant tumor architecture was follicular to glandular with intervening fibrous septa. The tumor cells were uniform cuboidal to polyhedral with abundant clear or eosinophilic cytoplasm. Immunohistochemically, the tumor cells were strongly positive for CK7, EMA, vimentin, SOX10, S-100, and focally positive for CA9. During 6 months of follow-up, there was no clinical or radiological evidence of recurrence or metastasis. CONCLUSION: SRCLC has microscopic features which overlap with tumors that contain clear cells. Thus, several other tumors must be considered in the differential diagnosis of a tumor of the sinonasal region with clear cells, especially metastatic renal clear cell carcinoma. SRCLC is an indolent tumor and none of the reported SRCLC patients had metastatic disease.